The Effect of Leg Length Plyometric Exercise on Increasing Volleyball Jump Power at Public Senior High School 1 Parigi Motong (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
The purpose of this study was to analyze the difference in effect between plyometric depth jump over barrier hops, and single leg box jumps on power jumps, analyzing the difference in effect between long legs and short legs to power jumps, analyze the interaction between plyometric exercise and leg length to power jump. The method used is a two-factor design 2 x 2 design experiment, dependent variables and effects caused by interaction, the sample used is purposive sampling 24 players in a total population of 30 players, criteria for men aged 17-20 years. MANOVA test analysis technique with SPSS 20 program and a significant level of 0.05%. The results of the study have an effect between plyometric depth jump over barrier hops, and single leg box jumps on the increase in power of significant value 0.00; there is influence between players who have leg length to increase the power jump ability of significant value 0.00; there is an interaction between plyometric exercise and leg length to increase the power jump capability of significant value 0.04. This data provides new findings on the exercises used in increasing power jumps, based on this data it can be concluded that there is an influence between plyometric depth jump over barrier hops and single leg box jumps on increasing power jumps and plyometric depth jump over barrier hops, there is the influence of players who have long legs better jump than players who have short legs, there is a plyometric exercise interaction to increase the player's power jump capability. The benefits can contribute to knowledge, especially understanding of the plyometric training method, against the power of volleyball player jumps in Public Senior High School 1 Parigi Motong Regency.